RUSSIAN LANGUAGE IN THE CONTEXT OF THE LINGUISTIC SITUATION IN UZBEKISTAN - V.A. Lyamkina (Многоязычие в образовательном пространстве)
The article examines the functioning of the Russian language in the context of Uzbekistan’s linguistic situation within the framework of scientific reflection. The research topic is relevant due to the current changes in the language environment of the state, including globalisation and political changes. This article aims to analyse the current status and perception of the Russian language in Uzbekistan by means of a sociological survey to identify the attitude towards the Russian language among the population. The analytical method, the method of logical analysis, the method of modelling and the method of questionnaire survey were applied in the work. The results, which represent a continuation of the author’s long-term research, allow us to draw a conclusion about the significant status of the Russian language in today’s Uzbekistan. The study can serve as a basis for the development of appropriate language policies and programmes.